Analisis Kebutuhan dan Strategi Penyediaan Energi Listrik di Provinsi Sulawesi Utara - Rachmawan Budiarto; Kusnanto Kusnanto; Yohana Rosita Lumi (Jurnal Penelitian Pendidikan IPA, 2022)
Electrical energy is an important requirement in the development of an area. North Sulawesi Province is one of the areas with rapid development. This is due to the establishment of a special industrial economic zone located in Bitung City. Special economic zones are a form of the Government of Indonesia's efforts to realize the vision of Indonesia Gold 2045. Thus, a new energy demand and supply prediction scenario is needed to overcome this. This study uses the End-Use method with two scenarios of demand and supply. The energy analysis software used is LEAP. The research data used consists of customer data, electricity consumption, North Sulawesi GRDP, list of installed power plants, plans for additional power plants. All data were obtained from various related agencies, including PT PLN, Department of Energy and Mineral Resources, BAPPEDA, BPS North Sulawesi. The results of the projection calculations for the Business as Usual (BaU) and Indonesia Emas 2045 demand scenarios have increased for all sectors. In the household sector the average growth was 6.00% and for business, public, and industry it was 3.00, 4.00 and 25.00%. The average growth for the projected energy demand for the Indonesia Gold 2045 scenario in all sectors is the same, which is 5.00%. In the BaU supply scenario, it is still dominated by PLTD, PLTU, PLTA, and PLTP, while in the Indonesia Gold 2045 scenario, PLTA has increased.